Plan de negocios para la creación de una aplicación para el transporte de estudiantes a Universidades con tarifas reducidas en rutas compartidas en el distrito metropolitano de Quito - Rodríguez Zavala, Mateo Marcelo (2023)
The thesis focuses on analyzing the impact and evolution of Mybus, a shared transportation platform, in the transportation sector, as well as its implications for users, drivers, and urban mobility in general. The main objective of this study is to assess the feasibility and sustainability of Mybus as a transportation alternative in urban environments, considering its business model, market penetration, and regulatory challenges. The proposed hypothesis suggests that Mybus has succeeded in transforming the dynamics of urban mobility by providing a more convenient and accessible option compared to traditional methods of transportation.